2021
DOI: 10.3390/insects12070596
|View full text |Cite
|
Sign up to set email alerts
|

Ligusticum sinense Nanoemulsion Gel as Potential Repellent against Aedes aegypti, Anopheles minimus, and Culex quinquefasciatus (Diptera: Culicidae)

Abstract: Ligusticum sinense Oliv. cv. is a species of Umbelliferae (Apiaceae), a large plant family in the order Apiales. In this study, L. sinense hexane extract nanoemulsion gel (LHE-NEG) was investigated for mosquito repellency and compared to the standard chemical, N,N-diethyl-3-methylbenzamide (DEET), with the goal of developing a natural alternative to synthetic repellents in protecting against mosquito vectors. The results demonstrated that LHE-NEG afforded remarkable repellency against Aedes aegypti, Anopheles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…stephensi with different extracts from Citrullus vulgaris . Recently, Junkum et al [ 46 ] found that the hexane extract of Ligusticum sinense afforded remarkable repellency against Aedes aegypti , An. minimus , and C. quinquefasciatus , with median protection times of 5.5, 11.5, and 11.25 h, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…stephensi with different extracts from Citrullus vulgaris . Recently, Junkum et al [ 46 ] found that the hexane extract of Ligusticum sinense afforded remarkable repellency against Aedes aegypti , An. minimus , and C. quinquefasciatus , with median protection times of 5.5, 11.5, and 11.25 h, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The repellent activity of EO-based nano-emulsions and gels has been largely investigated for insect vector management [48][49][50], though they may also be exploited for stored product pest control [51]. The area-preference trials highlighted good repellent activity toward T. confusum of the majority of the developed gels.…”
Section: Discussionmentioning
confidence: 99%
“…Undiluted essential oils were evaluated for repellency against female A. aegypti, A. dirus and C. quinquefasciatus using the arm-in-cage technique modified from the standard World Health Organization method [ 16 ] and Junkum et al [ 18 ]. Each essential oil was tested on adult healthy volunteers at random.…”
Section: Methodsmentioning
confidence: 99%
“…After 30 min post application, the tested arm was exposed for 3 min, then withdrawn for 30 min, and then exposed again. The experiment was stopped when the second mosquitoes landed on the test area and recorded as the complete-protection time for that subject [ 18 ]. The protection time was measured between the application of essential oil and the second landed.…”
Section: Methodsmentioning
confidence: 99%